Comparative Analysis of Key Performance Indicators (KPIs) in Government Hospitals Before and After the Implementation of Public Service Agency (BLU) Financial Management Status - Afif Wahyudi Hidayat (Journal of Health Service Administration and Hospital Management, 2026)
The transition of Indonesian government hospitals into Public Service Agencies (BLU) represents a pivotal shift in addressing bureaucratic stagnation within the public health sector. This study evaluates the impact of financial and managerial autonomy on Key Performance Indicators (KPIs) across 28 National Central General Hospitals (RSUP) in Indonesia. Utilizing a retrospective longitudinal design, secondary data from 2022–2024 were extracted from official Ministry of Finance and Ministry of Health repositories. The analysis focused on clinical efficiency, service quality, and financial sustainability metrics. Results indicate a transformative surge in operational performance, characterized by a significant increase in the mean Bed Occupancy Rate from 58.42% to 76.85% and a sharp decline in the Turn Over Interval from 3.50 to 1.82 days. Furthermore, the average financial self-sufficiency ratio escalated to 82.40%, demonstrating a reduced reliance on state subsidies. Clinical outcomes remained robust, with the Average Length of Stay decreasing to 5.25 days while the Gross Death Rate showed a downward trend to 38.50 per 1,000 discharges. These findings imply that institutional flexibility, supported by performance-based remuneration and independent procurement, catalyzes healthcare modernization and fiscal resilience. In conclusion, the BLU framework successfully harmonizes sound business practices with public service mandates. Future research should explore the integration of artificial intelligence and digital health ecosystems to further optimize governance. This study provides a vital benchmark for public hospital reforms across emerging economies in Southeast Asia.